ANALYSIS OF UTOPIAN REPRESENTATION IN THE CHRONICLES OF NARNIA: THE LION, THE WITCH, AND THE WARDROBE - Koe Hua, Junipa Andini Betsyeba; Sriastuti, Anna (JOLALI: Journal of Language and Literature, 2025)
The Chronicles of Narnia: The Lion, The Witch, and The Wardrobe is a well-known novel, that tells the story of four children who found a magical world of Narnia through a wardrobe. It is also known that this novel is an allegory to the story of Jesus Christ. However, this study aims to apply Stuart Hall's representation theory to examine how an allegory of a utopian world is portrayed in C. S. Lewis's The Chronicles of Narnia: The Lion, The Witch, and The Wardrobe. To demonstrate the contrast between utopia and dystopia, symbols from the narrative are analyzed, including Aslan, the White Witch, the wardrobe, the Pevensie siblings, and the transition from winter to spring. Lewis uses these symbols to create his conceptual universe based on morality, justice, and the possibility of redemption in the face of tyranny. In contrast to the White Witch's oppressive control over the dystopian Narnia she governs, Aslan embodies selfless love and leadership. By providing a bridge between the actual world and the Narnia imagination, the wardrobe highlights the ideas of bravery and transformation for the viewer. These issues make it possible to comprehend how The Lion, the Witch, and the Wardrobe both perform a Christian allegory and provide a broad representation of an ideal society that can be established via selflessness, solidarity, and moral self-control.